A newlywed's guide to fortune and murder - Freeman, Dianne, 1958- (Freeman, Dianne, 1958- Countess of Harleigh mystery, 2023)
"With her new husband George busy on a special mission for the British Museum, Frances has taken on an assignment of her own. The dowager Viscountess Wingate needs someone to sponsor her niece, Kate, for presentation to Queen Victoria. Frances--who understands society's quirks and constraints as only an outsider can--is the perfect candidate. Kate is charming and intelligent, though perhaps not quite as sheltered as she might first appear. More worrying to Frances is the viscountess's sudden deterioration. The usually formidable dowager has become shockingly frail, and Frances suspects someone may be drugging her. The spotlight falls on Kate, who stands to inherit if her aunt passes, yet there are plenty of other likely candidates within the dowager's household, both above and belowstairs. Joining forces with her beloved George, Frances comes to believe that the late viscount, too, was targeted. And with the dowager seeming to be in greater danger every day, they must flush out the villain before she follows in her husband's footsteps, directly to the grave..."--